Determination of the Optimum Excitation Wavelength for the Parathyroid Gland Using a Near-Infrared Camera - Tabei, Isao; Fuke, Azusa; Fushimi, Astushi; Takeyama, Hiroshi (Frontiers in Surgery, 2021)
When performing thyroid/parathyroid surgery, difficulty detecting the parathyroid gland is a common experience because it is frequently mistaken with surrounding structures, including the thyroid gland, lymph nodes, and fat. To obtain successful surgical results, the auto fluorescent property of the parathyroid gland occurring at 820–830 nm has been used. Intraoperative visualization and detection by fluorescence enable protection of the gland from damage and removal. Use of a near-infrared (NIR) camera has been proposed to indicate the parathyroid gland, but the devices and success rates have varied. This study aimed to define optimum excitation wavelength (EWL) by measuring the EWL of the surgically removed parathyroid gland for its autofluorescence. Glands were exposed to EWL at 10-nm intervals from 670–790 nm with a light-emitting diode monochromator; autofluorescence intensity was recorded with a conventional NIR video camera. Autofluorescence intensity curves of three normal parathyroid glands were depicted; the optimum EWL was measured as 760–770 nm. Also, the illumination of the surrounding structures were compared at the optimum EWL. The auto fluorescent intensity of the parathyroid gland was 2-fold greater than for surrounding structures. This difference in fluorescence intensity should enable distinction of the parathyroid gland from surrounding structures. The clarification of the optimum EWL can guide refinements of the NIR camera for better surgical outcomes by improving detection of the parathyroid glands. Also, an understanding of optimum EWL should lead to developments for microscopic devices to unravel the still unknown mechanisms of the intrinsic autofluorescence of the parathyroid gland.